Dany jest ciąg o wyrazie ogólnym an= (-1)^n * (25-9n^2). Różnica a2-a1 jest równa:

A) -37
B) -16
C) -5
D) 5
Podaj całe rozwiązanie



Odpowiedź :

Odpowiedź:

D

Szczegółowe wyjaśnienie:

[tex]a_{2} -a_{1} =(-1)^{2} *(25-9*2^{2}) - (-1)^{1} *(25-9*1^{2} )= (25-36)+(25-9)=-11+16=5[/tex]

[tex]a_{n} = (-1)^{n}\cdot(25-9n^{2})\\\\a_1 = (-1)^{1}\cdot(25-9\cdot1^{2}) = -1\cdot(25-9) = -1\cdot16 = -16\\\\a_2 = (-1)^{2}\cdot(25-9\cdot2^{2}) = 1\cdot(25-9\cdot4) = 25-36 = -11\\\\a_2 - a_1 = -11-(-16) = -11+16 = 5\\\\Odp. \ D)[/tex]